(untitled) (International Journal of Environmental Sciences, 2025)
This study examines the impact of teachers’ questioning techniques on the speaking performance of English as a Foreign Language (EFL) students at Dong Nai Technology University, Vietnam. In response to a growing emphasis on communicative competence within higher education, the research investigates how referential versus display questions and open versus closed questions relate to students’ speaking fluency, accuracy, complexity, and motivation. A quantitative correlational design was employed, involving 210 non-English-major students. Data were collected through structured speaking tasks and classroom observations of teacher questioning patterns, coded using validated frameworks. Statistical analyses, including Pearson correlations and multiple regression, revealed that referential and open-ended questions were significantly associated with higher levels of fluency, accuracy, complexity, and student motivation to participate in speaking tasks. Conversely, display and closed questions showed negligible or negative associations with these indicators. The findings support international literature emphasizing the pedagogical value of communicative questioning strategies and highlight a gap in their application within the Vietnamese tertiary context. The study provides practical implications for teacher training and curriculum reform aimed at fostering oral proficiency through more effective classroom discourse. Recommendations for future research include longitudinal studies and mixed-method designs to explore the long-term effects of questioning strategies on language development.